Snapshot of Adaptive Management in Peacebuilding Programs - Queen, Emily Forsyth; Baumgardner-Zuzik, Jessica; Hume, Elizabeth; Greenberg, Melanie (Alliance for Peacebuilding, 2018)
The Alliance for Peacebuilding developed the report Snapshot of Adapti ve Management in Peacebuilding Programs with support from Humanity Uni ted. This report examines how existing organizational programs are des igning and learning from adaptive management in a conflict effected an d fragile states. It further provides practical recommendations for ap plying adaptive management to peacebuilding programs based on synthesi s … Continue reading "Snapshot of Adaptive Management in Peacebuilding Programs"
Keywords: KEY